Mannan-Rich Fractions in Poultry Nutrition: A Sustainable and Defensive Strategy against Antimicrobial Resistance - Jai Gopal Sharma; Simran Kumari; Priyanka Parmar (Recent Trends in Infectious Diseases, 2026)
Antimicrobial resistance (AMR) has evolved to be a significant global threat, menacing worldwide health and food security. Its proliferation in poultry farming has spurred the search for sustainable, non-antibiotic alternatives. One promising alternative is Mannan-Rich Fractions (MRFs), which is derived from Saccharomyces cerevisiae. These bioactive compounds not only support poultry health but also aid in suppressing pathogenic bacteria without contributing to resistance. This review brings together current studies highlighting how MRFs exert heterogenous actions, including competitive exclusion of pathogens, encouraging beneficial gut microbes, immunomodulation, and metabolic disruption in resistant bacteria. Research indicates that MRFs effectively lowers the intestinal loads of Escherichia coli, Salmonella enterica, and Campylobacter jejuni etc. While improving feed conversion ratio, villus height, and nutrient absorption. At the molecular level, MRFs influences many key enzymes involved in glycolysis, TCA cycle and induce reactive oxygen species (ROS) production in resistant E. coli thereby resensitizing them to antibiotics. When used alongside fermented feed ingredients or probiotics, MRFs further enhance immune gene expression, growth rate, and gut barrier integrity. Together, these findings positions MRFs as a powerful, natural solution for minimizing antibiotic usage in poultry farming. The integration of MRFs into poultry diets presents a promising alternative to conventional antibiotic use, aligning with global effort to contain AMR in Poultry.
Keywords: Poultry; Yeast Mannan Fraction; antimicrobial resistance; gut health; reactive oxygen species